Spiritual And Educational Basis Of Educating Youth In The Spirit Of Tolerance And International Harmony - Kadirjon Odilov (Global Scientific Publishing, 2023)
This article is devoted to the education of youth in the spirit of interethnic harmony and tolerance, the formation of youth spirituality, focusing on the fact that more than one hundred and thirty nations and nationalities living in the country participate in good deeds in this direction, since the future and stability and development of the country are closely connected with the education of youth in the spirit of interethnic harmony and tolerance.
Keywords: Youth; harmony; education; worldview